IMPACT OF JAKARTA MASS RAPID TRANSIT ON LOCAL AIR QUALITY (Pusat Penelitian, Badan Keahlian DPR RI, 2022)
Moda Raya Terpadu Jakarta, or MRT Jakarta, is the first urban rail-based public transportation in Indonesia with several underground lines. Since March 24, 2019, MRT Jakarta Phase 1 (North-South corridor) has officially operated and has a line length of about 16 kilometers consisting of seven elevated stations and six underground stations. The motivation for this research stems from the fact that in 2019 Jakarta occupied ranked first as the capital city with the highest level of air pollution in Southeast Asia, where the land transportation sector is one of the primary sources. Government investment is significant enough to develop public transport, which is expected to overcome this market failure. However, research evidence to prove the benefits of MRT operation on local air quality is still limited, especially for urban areas in developing countries such as Jakarta. This study uses the Difference-in-Difference method and the Air Pollution Standard Index (ISPU) as air quality proxies by controlling several factors, such as weather conditions, determination of national holidays, weekends, and large-scale social restriction (PSBB) policies during the Covid-19 pandemic that hit all parts of the world, the gradual determination of MRT fares, and the period of construction of the MRT line. This study reveals two main findings. First, the operation of MRT Jakarta Phase 1 in corridor 1 resulted in a 27.4 percent reduction in air pollution levels in the area closest to the MRT line. Second, the estimation results show that the impact on reducing air pollution is negligible on weekends.Keywords: air quality, MRT Jakarta, ISPUAbstrakModa Raya Terpadu Jakarta, atau MRT Jakarta merupakan transportasi publik berbasis kereta perkotaan pertama di Indonesia dengan beberapa jalur bawah tanah. Sejak 24 Maret 2019, MRT Jakarta Fase 1 (koridor Utara-Selatan) resmi beroperasi dan memiliki panjang jalur sekitar 16 kilometer yang terdiri dari tujuh stasiun layang dan enam stasiun bawah tanah. Motivasi penelitian ini bermula dari kenyataan bahwa pada tahun 2019 Jakarta menduduki peringkat pertama sebagai ibu kota dengan tingkat polusi udara tertinggi di Asia Tenggara, di mana sektor transportasi darat menjadi salah satu sumber utama. Investasi pemerintah cukup besar untuk mengembangkan angkutan umum yang diharapkan dapat mengatasi kegagalan pasar ini. Namun, hasil penelitian untuk membuktikan manfaat pengoperasian MRT terhadap kualitas udara lokal masih terbatas, terutama untuk wilayah perkotaan di negara berkembang seperti Jakarta. Penelitian ini menggunakan metode Difference-in-Difference dan Indeks Standar Polusi Udara (ISPU) sebagai proksi kualitas udara dengan mengontrol beberapa faktor-faktor, seperti kondisi cuaca, penetapan hari libur nasional, akhir pekan, kebijakan pembatasan sosial berskala besar (PSBB) di masa pandemi Covid-19 yang melanda seluruh belahan dunia, penetapan tarif MRT secara bertahap, dan dengan memperhitungkan periode pembangunan jalur MRT. Penelitian ini mengungkapkan dua temuan utama. Pertama, beroperasinya MRT Jakarta Fase 1 di koridor 1 berdampak pada penurunan tingkat polusi udara sebesar 27,4 persen di area yang terdekat dengan jalur MRT. Kedua, hasil estimasi menunjukkan bahwa dampaknya terhadap penurunan polusi udara terjadi lebih kecil pada akhir pekan.Kata kunci: kualitas udara, MRT Jakarta, ISPU